Appendix C to "Systems engineering competencies and proficiency levels by role for an MBSE-enabled project" - Shaw, Sarah G., author (Colorado State University. Libraries, 2025)
Appendix C shows the total number of Knowledge, Skills, Abilities, and Behaviors (KSABs) in the Digital Engineering Competency Framework (DECF) v1.1 assigned to different roles in different team sizes for the System Requirements Definition and Traceability project.
Paper submitted for publication to the IEEE Open Journal of Systems Engineering, October 2025.
Keywords: model-based systems engineering (MBSE); digital engineering (DE); digital engineering competency framework (DECF); systems engineering (SE)